Anthropological tropes and historical tricksters: pilgrimage as an 'example' of persuasion. (May 2015) - Coleman, Simon; BANDAK, ANDREAS; HØJER, LARS
<x xml:space="preserve">Abstract</x> I explore the implications of example‐making for both informants and ethnographers through an analysis of the history of the refoundation of the Anglican shrine at Walsingham during the twentieth century. I argue for an appreciation of distinctions between examples as 'models' and 'instances', but also for a focus on relations between the inchoate and the specific in processes of exemplification. The paper shows how an examination of the making of examples by actors in the field can speak to the creation of examples in writing and analysis, and may introduce elements of 'serendipity' more normally associated with encounters in the field.